2009
DOI: 10.1534/genetics.109.103192
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Strata in a Small Mating-Type-Specific Region of the Smut Fungus Microbotryum violaceum

Abstract: DNA sequence analysis and genetic mapping of loci from mating-type-specific chromosomes of the smut fungus Microbotryum violaceum demonstrated that the nonrecombining mating-type-specific region in this species comprises 25% (1 Mb) of the chromosome length. Divergence between homologous mating-type-linked genes in this region varies between 0 and 8.6%, resembling the evolutionary strata of vertebrate and plant sex chromosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 34 publications
2
83
2
Order By: Relevance
“…However, in many cases, each haploid individual has a mating type, genetically determined by the mating type locus, and individuals must be of opposite mating types to mate successfully. In fungi such as Neurospora tetrasperma, Microbotryum violaceum and Cryptococcus neoformans, each haploid genome contains a single copy of the mating type locus and meiotic recombination within the mating type locus is suppressed [110][111][112]. In these fungal mating type chromosomes, recombination is suppressed over a region extending far beyond the mating type genes.…”
Section: Expansion Of the Non-recombining Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many cases, each haploid individual has a mating type, genetically determined by the mating type locus, and individuals must be of opposite mating types to mate successfully. In fungi such as Neurospora tetrasperma, Microbotryum violaceum and Cryptococcus neoformans, each haploid genome contains a single copy of the mating type locus and meiotic recombination within the mating type locus is suppressed [110][111][112]. In these fungal mating type chromosomes, recombination is suppressed over a region extending far beyond the mating type genes.…”
Section: Expansion Of the Non-recombining Regionmentioning
confidence: 99%
“…In these fungal mating type chromosomes, recombination is suppressed over a region extending far beyond the mating type genes. Although they do not show the levels of gross heteromorphy observed in some animal and plant sex chromosomes, the occurrence of strata [111,112] indicates that expansion of the non-recombining region in these fungal chromosomes has occurred in several stages. In the absence of distinct sexes, expansion of the nonrecombining regions of fungal mating type chromosomes cannot be attributed to sexual antagonism as such, although, in theory, antagonistic processes may occur due to differences in ....Pr ospects & Overviews J. E. Ironside fitness optima between fungal mating types.…”
Section: Expansion Of the Non-recombining Regionmentioning
confidence: 99%
“…Similar processes are expected to occur in other nonrecombining regions, such as plant self-incompatibility loci and fungal mating-type loci. Indeed, it has been suggested that mating-type-determining regions of fungi, such as Cryptococcus neoformans (Lengeler et al, 2002), Neurospora tetrasperma (Menkis et al, 2008) and Microbotryum violaceum (Hood, 2002;Votintseva and Filatov, 2009), represent fungal 'sex chromosomes'. However, at present there is no solid evidence for genetic degeneration in fungal mating-type-determining regions.…”
Section: Introductionmentioning
confidence: 99%
“…The fungus has a bipolar heterothallic breeding system, and conjugation occurs only between sporidia of opposite mating types. The two mating types, A1 and A2, are determined by a mating-type-specific region, which is similar to the Y chromosomes of animals and plants, as recombination is suppressed in a large region around the mating-type-determining genes (Hood, 2002;Votintseva and Filatov, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation